Advances in Synthesis and Anti-Alzheimer’s Disease Potential of Functionalized Benzofurans: A Recent Overview - Kushwaha, Pragati; Rashi, Rashi; Bhardwaj, Ayush; Khan, Danish (Synlett, 2025)
Alzheimer’s disease (AD) comes under progressive neurodegenerative disorders which is the leading cause of dementia affecting the aged population. The available drugs for AD treatment are just palliative and not curative, further these drugs have severe side effects. Therefore, there is a significant demand for novel, potent, and safe molecules as anti-Alzheimer’s disease agents with diverse mechanisms of action. Benzofuran derivatives are one of the versatile and ubiquitous scaffolds being developed as potential candidates against AD. While benzofuran analogues have not yet resulted in widely approved AD treatments, these molecules remain a significant focus of AD drug discovery because of their multitargeted approach and promising preclinical results. The ongoing research into these molecules holds potential for future clinical applications as anti-AD agents. In light of this, the present review outlined recent advances of the synthesis and potent anti-AD activities reported. The sole purpose of this review is to shed light on the design and development of these molecules with high efficacy and reduced toxicity against AD.1 Introduction2 Synthesis3 Benzofuran-Based Scaffolds against AD4 Naturally Occurring Benzofurans for Treatment of AD5 Future Perspectives6 Conclusion
Keywords: benzofuran; synthesis; electrochemical; Alzheimer’s disease; AChE; β-amyloid